Geochemical nature of the geothermal water from Lanzhou Basin: Implications for the genesis of shallow helium-bearing fluids - Jianzhou TANG; Shuangming WANG; Zhicheng ZHANG; Ke LI; Changpeng LI (Meitian dizhi yu kantan)
Objective and Methods Investigations on the geochemical nature of geothermal water are vital to the comprehension of the origin of helium-rich fluids in shallow basins. To address this issue, this paper reports the results of the chemical analysis, H-O isotopes and 14C ages from geothermal water and soluble gas components from the well BY-1 in Lanzhou Basin, northeastern margin of Qinghai Tibet Plateau. Chemical analysis of geothermal water samples reveals that the chemical type of geothermal water is NaCl. The show δD value of −78‰, high δ18O value (−8.7‰), low 3H value (<0.4TU), and old 14C age (20.50±0.92ka). The geothermal water has undergone evaporation-concentration and water-rock interactions, which originated from ancient atmospheric precipitation. Component analysis from 10 water-dissolved gas samples reveals an average helium concentration of 0.44%. The concentration of He meets the standard for helium-rich gas fields. Compositions of the dissolved gas and the geochemical nature of the groundwater jointly suggest that the associated helium in the geothermal water from this well is a product of the radioactive decay of Th-U elements in the basement rocks of the basin. Comprehensive analysis indicates that the upward migration and accumulation of ancient helium-bearing water from the basement into shallow geothermal reservoirs along fault zones under the background of tectonic uplift is the key process for the enrichment of associated helium in geothermal water in the Lanzhou Basin.